Enamel Defects Associated With Dentin Sialophosphoprotein Mutation in Mice - Liang, Tian; Xu, Qian; Zhang, Hua; Wang, Suzhen; Diekwisch, Thomas G. H.; Qin, Chunlin; Lu, Yongbo (Frontiers in Physiology, 2021)
Dentin sialophosphoprotein (DSPP) is an extracellular matrix protein that is highly expressed in odontoblasts, but only transiently expressed in presecretory ameloblasts during tooth development. We previously generated a knockin mouse model expressing a mouse equivalent (DSPP, p.P19L) of human mutant DSPP (p.P17L) (referred to as “DsppP19L/+”), and reported that DsppP19L/+ and DsppP19L/P19L mice manifested a dentin phenotype resembling human dentinogenesis imperfecta. In this study, we analyzed pathogenic effects of mutant P19L-DSPP on enamel development in DsppP19L/+ and DsppP19L/P19L mice. Micro-Computed Tomography (µCT) analyses of 7-week-old mouse mandibular incisors showed that DsppP19L/P19L mice had significantly decreased enamel volume and/or enamel density at different stages of amelogenesis examined. Acid-etched scanning electron microscopy (SEM) analyses of mouse incisors demonstrated that, at the mid-late maturation stage of amelogenesis, the enamel of wild-type mice already had apparent decussating pattern of enamel rods, whereas only minute particulates were found in DsppP19L/+ mice, and no discernible structures in DsppP19L/P19L mouse enamel. However, by the time that incisor enamel was about to erupt into oral cavity, distinct decussating enamel rods were evident in DsppP19L/+ mice, but only poorly-defined enamel rods were revealed in DsppP19L/P19L mice. Moreover, µCT analyses of the mandibular first molars showed that DsppP19L/+ and DsppP19L/P19L mice had a significant reduction in enamel volume and enamel density at the ages of 2, 3 and 24 weeks after birth. Backscattered and acid-etched SEM analyses revealed that while 3-week-old DsppP19L/+ mice had similar pattern of enamel rods in the mandibular first molars as age-matched wild-type mice, no distinct enamel rods were observed in DsppP19L/P19L mice. Yet neither DsppP19L/+ nor DsppP19L/P19L mice showed well-defined enamel rods in the mandibular first molars by the age of 24 weeks, as judged by backscattered and acid-etched SEM. In situ hybridization showed that DSPP mRNA level was markedly reduced in the presecretory ameloblasts, but immunohistochemistry revealed that DSP/DSPP immunostaining signals were much stronger within the presecretory ameloblasts in Dspp mutant mice than in wild-type mice. These results suggest that mutant P19L-DSPP protein caused developmental enamel defects in mice, which may be associated with intracellular retention of mutant DSPP in the presecretory ameloblasts.